The relationship between smoker status and oxygen saturation values after general anesthesia in the operating room installation at RSD Mangusada Badung in 2021 - ketut sudiani (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
In the implementation of anesthesia especially general anesthesia, The adequacy of oxygen in the blood is absolutely necessary, the presence of obstructions can affect oxygen saturation is very need to be considered. The phenomenon that often occurs in smoking patients is partial or total airway obstruction because of mucus hypersecretion which if not handled properly can cause hypoxia. This study aims to determine the relationship between smoker status and oxygen saturation values after general anesthesia in the operating room installation at RSD Mangusada Badung in 2020. This type of research is quantitative with observational methods and cross sectional design, The sample in this study were all post-general anesthesia patients in the operating room installation of RSD Mangusada Badung according to the inclusion and exclusion criteria selected by purposive sampling as many as 44 respondents. The study was conducted for 1 month. The results obtained by most of the post general anesthesia patients were included in the moderate smoking category, namely 17 (38.6%) respondents and the mean value of oxygen saturation in post-general anesthesia patients in the Operating Room Installation at RSD Mangusada Badung was 98.14% Data were analyzed by the nonparametric spearman rank test at the significance level α 0.05, p values ​​were 0.000 <0.05. This shows that there is a significant relationship between smoking status and oxygen saturation values ​​in post-general anesthesia patients at the Operation Room Installation of RSD Mangusada Badung. It is expected that people can reduce or stop smoking to maintain the stability of oxygen saturation in the blood. Keywords: smoker status, oxygen saturation, general anesthesia